2008
DOI: 10.1038/ajh.2007.14
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Endothelial and Inducible Nitric Oxide Synthase Expression by Reactive Oxygen Species

Abstract: An increase in ROS activity upregulates NOS expression in vitro in HCAECs grown in culture, and also in vivo in animals. This effect appears to be, in part, mediated by limiting the availability of NO, thereby exerting a negative feedback influence on NOS expression through activation of NFkappaB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
92
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 33 publications
5
92
2
1
Order By: Relevance
“…A study by Zhen et al has suggested that ROS-stimulated upregulation of eNOS expression is mediated by diminished NO availability and consequent reduction in the negative feedback regulatory action of NO on eNOS expression, which is possibly mediated by NF-κ B. 39 In our present study, PJ treatment diminished the increased eNOS activity in diabetic lung most probably through NF-κ B inactivation.…”
supporting
confidence: 62%
“…A study by Zhen et al has suggested that ROS-stimulated upregulation of eNOS expression is mediated by diminished NO availability and consequent reduction in the negative feedback regulatory action of NO on eNOS expression, which is possibly mediated by NF-κ B. 39 In our present study, PJ treatment diminished the increased eNOS activity in diabetic lung most probably through NF-κ B inactivation.…”
supporting
confidence: 62%
“…Zhen and colleagues 52 showed apparent suppression of eNOS activity in human coronary artery endothelial cells and rats by the NO donor S-Nitroso-N-Acetyl-D,LPenicillamine (SNAP). This suggests NO exerts a negative feedback effect on eNOS expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of ROS/RNS, the inducible isoform of NOS (iNOS; coded by NOS2A) is upregulated by nuclear factor kappa B in the liver. 22,23 Due to the biological imperative of protecting the cellular environment against oxidative stress, ROS/RNS are rapidly eliminated by antioxidant enzymes such as GSTs, NAD(P)H dehydrogenase quinone 1 (NQO1; coded by NQO1), and heme oxygenase 1 (HO1; coded by HMOX1) in humans. 24 The expression of these genes, which carry an antioxidant-responsive element (ARE) in their promoter regions is regulated by several transcriptional factors, including nuclear factor erythroid 2-related factor 2 (Nrf2; coded by NFE2L2), BTB and CNC homology 1 (Bach1; coded by BACH1), and the small Maf basic leucine zipper proteins (MafF, MafG, and MafK).…”
Section: Introductionmentioning
confidence: 99%